Estudo da copolimerização de estireno e cardanol em meios homogêneo e heterogêneo - Galvão, Letícia de Albuquerque (2016)
In polymer industry, cardanol, a liquid byproduct of cashew nuts, has shown great potential. The main advantage of cardanol is the ability of changing materials hydrophobicity, and due to unsaturation, it is polymerizable. Besteti et al. (2011) showed the copolymer obtained by the reaction between styrene, a traditional monomer, and cardanol is promising as support for enzyme immobilization. Thus, this dissertation aims to study the kinetic behavior of cardanol and styrene copolymerization, through experiments using different polymerizations techniques and mathematical model developed to describe experimental data. It was possible to confirm styrene and cardanol copolymerization for mass, suspension, emulsion and suspension-emulsion polymerizations. It was also possible to observe an inhibitory effect caused by cardanol. The results using azobisisobutyronitrile (AIBN) initiator in the organic phase showed high reaction rates and high molar masses, minimizing the inhibition observed. Using sodium lauryl sulfate (SLS) in aqueous phase also caused polymer with high rates and high molar masses. The particles for enzyme immobilization support showed significant results, with specific area similar to commercial supports. The proposed kinetic model, without considering inhibitory effect and impurity, was not successful to describe kinetics behavior of styrene and cardanol copolymerization.